2018
DOI: 10.1186/s12937-018-0378-2
|View full text |Cite
|
Sign up to set email alerts
|

Progress of children with severe acute malnutrition in the malnutrition treatment centre rehabilitation program: evidence from a prospective study in Jharkhand, India

Abstract: BackgroundIn Jharkhand, Malnutrition Treatment Centres (MTCs) have been established to provide care to children with severe acute malnutrition (SAM). The study examined the effects of facility- and community based care provided as part the MTC program on children with severe acute malnutrition.MethodA cohort of 150 children were enrolled and interviewed by trained investigators at admission, discharge, and after two months on the completion of the community-based phase of the MTC program. Trained investigators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…In other Indian studies assessing progress following inpatient and/or community care for SAM, rates of recovery were often lower than recommended in SPHERE guidance, and relapse was common [4244]. For example, in a recent follow-up study of 150 children discharged from MTCs in Jharkhand, 52% of children had relapsed into severe wasting 2 months after discharge [45]. In light of these findings, scaling up outpatient RUTF treatment for children over 6 months without concurrently strengthening ICDS, WASH, and the social protection interventions that support the intergenerational prevention of undernutrition may not have the large effects on mortality predicted by the 2013 Lancet Maternal and Child Nutrition Series in India and other South Asian contexts [17].…”
Section: Discussionmentioning
confidence: 99%
“…In other Indian studies assessing progress following inpatient and/or community care for SAM, rates of recovery were often lower than recommended in SPHERE guidance, and relapse was common [4244]. For example, in a recent follow-up study of 150 children discharged from MTCs in Jharkhand, 52% of children had relapsed into severe wasting 2 months after discharge [45]. In light of these findings, scaling up outpatient RUTF treatment for children over 6 months without concurrently strengthening ICDS, WASH, and the social protection interventions that support the intergenerational prevention of undernutrition may not have the large effects on mortality predicted by the 2013 Lancet Maternal and Child Nutrition Series in India and other South Asian contexts [17].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively lower rates of weight gain observed in this study could be due to multiple factors such as frequent morbidities in hospitalized children, reducing the weight gain by almost about 40 per cent; admission of moderately wasted children (due to being at high risk of SAM) and lower intake of potassium, magnesium, etc , and have been discussed elsewhere6889. Studies at various Nutritional Rehabilitation Centres (NRCs) have shown rates of weight gain in the range of about 5-10 g/kg/day9091. Due to concerns about disproportionately higher amounts of body fat deposition during rapid weight gain of children recovering from SAM, a study at our ward examined the composition of weight gain during nutrition rehabilitation in 80 children (aged 6-60 months)92.…”
Section: Catch-up Growth and Composition Of Weight Gainmentioning
confidence: 65%
“…They should also be motivated to translate the acquired knowledge into actions. Prior evidence suggests that caregivers may not adopt the practices even after education sessions by healthcare staff in the facilities (53) . Therefore, multiple sessions on nutrition and health education using behaviour change and communication materials are recommended to overcome this issue.…”
Section: Discussionmentioning
confidence: 99%